2012
DOI: 10.1016/j.jplph.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Reduced translocation of cadmium from roots is associated with increased production of phytochelatins and their precursors

Abstract: SummaryCadmium (Cd) is a non-essential trace element and its environmental concentrations are approaching toxic levels, especially in some agricultural soils. Understanding how and where Cd is stored in plants is important for ensuring food safety. In this study, we examined two plant species that differ in the distribution of Cd among roots and leaves. Lettuce and barley were grown in nutrient solution under two conditions: chronic (4 week) exposure to a low, environmentally relevant concentration (1.0 µM) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 50 publications
5
15
1
Order By: Relevance
“…This finding was similar with the report by Aina et al (2007), where a significant induction of PC 3 was detected in the roots of plants exposed to 100 lmolÁL -1 Cd. In contrast to our results, Akhter et al (2012) reported that PC 2 being 1-2 orders of magnitude higher than those of PC 3 and PC 4 in barley roots upon chronic exposure to 1.0 lmolÁL -1 CdCl 2 . The discrepancy indicates crop-specific responses of PCs to Cd toxicity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding was similar with the report by Aina et al (2007), where a significant induction of PC 3 was detected in the roots of plants exposed to 100 lmolÁL -1 Cd. In contrast to our results, Akhter et al (2012) reported that PC 2 being 1-2 orders of magnitude higher than those of PC 3 and PC 4 in barley roots upon chronic exposure to 1.0 lmolÁL -1 CdCl 2 . The discrepancy indicates crop-specific responses of PCs to Cd toxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…and Cu 2? in the nutrient solution (Akhter et al 2012). Recent studies have shown that PCs could undergo long-distance transport in the root-to-shoot and shoot-to-root directions (Chen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochelatins (PCs) are a family of peptides with the structure (c-Glu-Cys)n-Gly, where n represents the repetition of g-Glu-Cys, which tends to vary from 2 to 11 (Akhter et al 2012). As with other metals, PCs play an important role in Cd detoxification (Márquez-García et al 2011;Choppala et al 2014).…”
Section: Phytochelatinsmentioning
confidence: 99%
“…Phytochelatins are reported to neutralize harmful effects by chelating metals with their SH groups. Of all the heavy metals, Cd 2+ has been observed to invoke the strongest activation of the phytochelatin synthase (PCS) and thus PC production (Akhter et al 2012) due to the high affinity of the thiol groups for Cd on the cysteine residues (Chekmeneva et al 2011). Chen et al (2007) studied Cd-PC complexes in Brassica chinensis and observed binding stoichiometries of 1:1 to 3:1 depending on the availability of thiol groups and Cd 2+ in the cytosol.…”
Section: Phytochelatinsmentioning
confidence: 99%